Strengthening teachers’ digital competencies through AI-based Learning Design training in remote areas - Maya Pujowati; Rani Puji Lestari; Renes; Tri Suwarningsih; Etty Octaviani Manalu; Agus Sunaryo (University of Merdeka Malang, 2026)
Limited digital literacy and restricted access to technology training remain major challenges for teachers in disadvantaged, remote, and outermost (3T) areas, particularly in supporting the implementation of the Merdeka Curriculum. At SD Negeri Gudang Garam, Keerom Regency, most teachers had limited experience using Artificial Intelligence (AI) tools for administrative and instructional purposes. This community service program aimed to strengthen teachers’ digital competencies through practical training and mentoring in the use of AI-based applications for learning design and educational administration. The program involved 12 teachers and was implemented through needs identification, intensive hands-on training, mentoring, and evaluation activities. Teachers were introduced to AI tools such as ChatGPT and Canva AI to develop digital lesson plans, interactive visual media, and AI-assisted learning videos adapted to local classroom contexts. The results showed improvements in teachers’ understanding and practical skills in utilizing AI for instructional purposes. Teachers successfully produced adaptive digital lesson plans, visual learning materials, and instructional videos directly applicable in classroom activities. The program also increased teachers’ confidence and creativity in integrating digital technology into teaching despite limited infrastructure and unstable internet access. To support sustainability, offline learning modules and local teacher learning communities were strengthened to encourage continuous collaboration and independent learning after program completion